2016
DOI: 10.5649/jjphcs.42.14
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Vancomycin Therapy by the Protocol-Based Pharmacotherapy Management (PBPM) including TDM-Order

Abstract: Vancomycin (VCM) is a first-line antibiotic used for methicillin-resistant Staphylococcus aureus (MRSA), and therapeutic drug monitoring (TDM) is recommended to minimize the risk of nephrotoxicity and ensure successful therapeutic outcomes. In Kyoto University Hospital, we have developed a new approach of pharmacist intervention in the medication with VCM, which is named "Protocol-Based Pharmacotherapy Management (PBPM)." PBPM is based on a protocol approved in a hospital committee, which mentioned that pharma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…6 We conducted a literature search using the keyword 'PBPM' through J-STAGE, which is the Japanese database for scientific research that covers more than 2000 electronic journals, and found eight articles reporting that PBPM is reducing the burden for physicians, nurses and entire institutions, as well as increasing medication safety and patient satisfaction. [7][8][9][10][11][12][13][14] The new role for Japanese pharmacists in the team approach has expanded primarily among hospital pharmacists via PBPM. However, we propose that in our modern, aging society, the functions and roles of pharmacists practising in community pharmacies need to Box 1 Roles and functions that a pharmacist should provide in the team approach As a team member, the pharmacist may:…”
Section: Dear Editormentioning
confidence: 99%
“…6 We conducted a literature search using the keyword 'PBPM' through J-STAGE, which is the Japanese database for scientific research that covers more than 2000 electronic journals, and found eight articles reporting that PBPM is reducing the burden for physicians, nurses and entire institutions, as well as increasing medication safety and patient satisfaction. [7][8][9][10][11][12][13][14] The new role for Japanese pharmacists in the team approach has expanded primarily among hospital pharmacists via PBPM. However, we propose that in our modern, aging society, the functions and roles of pharmacists practising in community pharmacies need to Box 1 Roles and functions that a pharmacist should provide in the team approach As a team member, the pharmacist may:…”
Section: Dear Editormentioning
confidence: 99%